A study on lean manufacturing implementation at metal products industry for small medium enterprises (SMEs) - Nurul Azimah, Othman (2012)
This final year project presents an exploratory study of lean manufacturing implementation in metal product industry for Small and Medium Enterprises (SMEs). A questionnaire is used to explore the extent of lean manufacturing implementation. This study also examines the reasons and critical factors that influence the implementation of lean manufacturing. The survey was performed on ten companies of SMEs. The respondents were chosen from those who are directly involved with producing metal product for large company at Malaysia. The findings show that most of the respondent companies are classified as non-lean manufacturing practice. These non-lean companies have low mean values for each of the fifteen lean manufacturing practices. These companies believe that the main reasons for them to the implementation of lean manufacturing are the desire to improve long term cost competitiveness and to meet customer demand. The results from this survey also revealed the main critical factor that prevent or delay the lean implementation. The main critical factor to implement lean manufacturing system is the lack of understanding lean concepts.